Perbedaan Kemampuan Berpikir Spasial Siswa berdasarkan Gender di SMA Muhammadiyah 1 Karanganyar - At tamimi, Ghulam Abas; Wardhani, Puspita Indra; Dewi, Ratih Puspita; Widiyatmoko, Wahyu; Wibowo, Yunus Aris (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
Spatial thinking ability in the 21st century is crucial for students to respond to challenges and global competition. While each student possesses different spatial thinking abilities, these abilities are also vulnerable to decline due to the uncertain global conditions. This study aims to analyze spatial thinking abilities based on students' gender through the Spatial Thinking Ability Test (STAT). The research employs a comparative method with quantitative data analysis using a two-sample t-test. The subjects of this study were male and female students at Muhammadiyah Senior High School 1 Karanganyar. Data collection was carried out using a test. The results showed that the average spatial thinking ability score for male students was 181.45, while female students scored 139.10. The Asymp. Sig. (2-tailed) value of 0.000, with a significance value (sig.) < 0.05, indicates that the alternative hypothesis (Ha) is accepted, while the null hypothesis (H0) is rejected. In conclusion, there is a significant difference in spatial thinking abilities, suggesting that male students at Muhammadiyah Senior High School 1 Karanganyar tend to have higher spatial thinking abilities than female students.